2019
DOI: 10.1021/acsami.9b10001
|View full text |Cite
|
Sign up to set email alerts
|

New Functionality of Ionic Liquids as Lubricant Additives: Mitigating Rolling Contact Fatigue

Abstract: Oil-soluble ionic liquids (ILs) have recently been demonstrated as effective lubricant additives of friction reduction and wear protection for sliding contacts. However, their functionality in mitigating rolling contact fatigue (RCF) is little known. Because of the distinct surface damage modes, different types of surface protective additives often are used in lubricants for sliding and rolling contacts. Therefore, the lubricating characteristics and mechanisms of ILs learned in sliding contacts from the earli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…Among them, the friction-reducing and anti-wear additives play an indispensable role in alleviating the friction and wear of the contact area by forming a physical adsorption/deposition film and/or tribochemical reaction film on the rubbing surfaces [28][29][30][31][32][33][34]. The traditional friction-reducing and anti-wear additives are usually composed of organic polar materials, such as organic molybdenum compounds [35][36][37], polymers [38], alcohols [39], esters [40][41][42], amine compounds [43], organic salts [44], ionic liquids, and their derivatives [45][46][47][48][49][50]. The strong polarity allows them to form neat adsorption films on the metallic rubbing surfaces to reduce the friction and wear of friction pairs.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the friction-reducing and anti-wear additives play an indispensable role in alleviating the friction and wear of the contact area by forming a physical adsorption/deposition film and/or tribochemical reaction film on the rubbing surfaces [28][29][30][31][32][33][34]. The traditional friction-reducing and anti-wear additives are usually composed of organic polar materials, such as organic molybdenum compounds [35][36][37], polymers [38], alcohols [39], esters [40][41][42], amine compounds [43], organic salts [44], ionic liquids, and their derivatives [45][46][47][48][49][50]. The strong polarity allows them to form neat adsorption films on the metallic rubbing surfaces to reduce the friction and wear of friction pairs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the ashless phosphonium-organophosphate ILs have shown less adverse impact effects on the emission catalysts compared to the conventional ZDDP and therefore replacing half the amount of ZDDP potentially reduces the exhaust emissions . Our recent study on the effect of ILs on rolling contact fatigue (RCF) revealed suppression of RFC surface damage and associated vibration noise by introducing a phosphonium-organophosphate IL to the gear oil …”
Section: Introductionmentioning
confidence: 99%
“…20 Our recent study on the effect of ILs on rolling contact fatigue (RCF) revealed suppression of RFC surface damage and associated vibration noise by introducing a phosphonium-organophosphate IL to the gear oil. 21 The objective of this research is to continue to develop ILadditized engine oils by further reducing the oil viscosity grade to SAE 0W-12 and optimizing the oil formulation by understanding the compatibilities between the IL+ZDDP combination and other additives including friction modifiers, detergents, dispersants, and antioxidants. A couple dozen of GF-6 compatible experimental formulations were designed for using the hybrid IL+ZDDP antiwear additives and screened using bench-scale tribological testing and analysis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…3 The surface property (wettability) of ILs was evaluated using contact angle measurements, and their evolvement in forming the protective tribofilms has been demonstrated using post-test chemical analysis techniques. 2,3,6,11 However, there is a lack of molecular-level understanding of their adsorption excess behavior at the lubricant oil/solid interface, which is needed to better utilize their capabilities.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Friction and wear of machines and moving parts pose energy and material loss problems for the global economy. , Lubrication therefore plays an important role in reducing friction and wear, increasing energy efficiency and device reliability. In practice, base lubricant oils are mixed with various additives such as organic friction modifier, antiwear additive, detergent, antifoam, etc. to improve the lubrication efficiency. As a new class of additives, ionic liquids (ILs), particularly oil-soluble ones, have been studied recently and demonstrated to significantly improve the tribological performance. , Some of them have also shown good synergistic effects with zinc dialkyldithiophosphate (ZDDP), the most commonly used antiwear additive, , as well as with nanoparticles . The surface property (wettability) of ILs was evaluated using contact angle measurements, and their evolvement in forming the protective tribofilms has been demonstrated using post-test chemical analysis techniques. ,,, However, there is a lack of molecular-level understanding of their adsorption excess behavior at the lubricant oil/solid interface, which is needed to better utilize their capabilities.…”
Section: Introductionmentioning
confidence: 99%